The effects of economic asymmetry in European Union in the context of international capital flows - Dominik Sadlakowski (Institute of Economic Research (IER), 2015)
In this article the author attempted to identify effects of the economic asymmetry in European Union in the context of international capital flows. The analysis concerns the effects of the functioning of the single European market, which are characterized by differing levels of economic development. According to the author this kind of asymmetry can lead to excessive economic dependence from leaders of this organization. In order to verify this statement in this article the author was based on data from Eurostat, UNCTAD, industry reports and available literature.
Keywords: E01; E22; F21; F36; F52; 330; foreign direct investment; European single market; the economic asymmetries